News from nowhere, or, An epoch of rest being some chapters from a utopian romance - Morris, William 1834-1896 (Cambridge texts in the history of political thought, 1995)
News from Nowhere (1890) is the most famous work of one of the greatest British writers and thinkers, William Morris. It is a utopian picture of a future communist society, drawing on the work of Ruskin and Marx and written in response to what Morris saw as soulless and mechanical visions of socialism. In this work of his last years, Morris distilled many of his leading ideas on politics, art and society, imagining a world in which capitalism has been abolished by a workers' revolution and nature and society have become beautiful habitations for humanity. In an era that has seen the collapse of state socialism, Morris's damning critique of this conception, and his positing of a powerful alternative, have important contemporary resonances